The emperor's children - Messud, Claire, 1966- (New York : Vintage Books, 2007)
Three friends, Marina Thwaite, Danielle, and Julius, struggling to make their way in New York City, find their friendship tested when an idealistic college dropout comes to town, changing the friend's lives forever.
Adult
Keywords: College dropouts -- Fiction; Friendship -- Fiction; Dropouts -- Fiction; Friendship -- Fiction; Love stories; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction